Risk Assessment of Terrorism - Tinnes, Judith (Perspectives on terrorism, 2024)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on risk assessment of terrorism. It includes literature on evaluation of threats emanating from terrorist/extremist individuals, groups, and ideologies. The bibliography focuses on recent publications (up to January 2024) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text as well as reference retrieval systems have been employed to broaden the search.